Evidence E - CCAFS Altmetrics data as per 2018 for SMO - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Publication list FOR CCAFS Almetrics for the SMO report of 2018